1999
DOI: 10.1164/ajrccm.159.5.9807059
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Reaction in Pulmonary Muscular Arteries of Patients with Mild Chronic Obstructive Pulmonary Disease

Abstract: Endothelial dysfunction and intimal thickening have been shown in pulmonary arteries (PA) of patients with mild chronic obstructive pulmonary disease (COPD). To investigate whether an inflammatory process related to tobacco smoking might be involved in the development of pulmonary vascular abnormalities in COPD, we characterized the inflammatory cell infiltrate and the endothelium-dependent relaxation in PA of 39 patients who underwent lung resection, divided into three groups: "nonsmokers" (n ϭ 7); "smokers,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
201
2
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(220 citation statements)
references
References 29 publications
(50 reference statements)
10
201
2
7
Order By: Relevance
“…This switch is important during resolution of vascular injury and homeostasis and appears to be regulated by different miRNAs [38,39]. Chronic inflammation and tissue hypoxia are thought to induce increased vascular growth by directly effecting the VSM cells [40] the result being muscularisation and thickening of the blood vessels [13,40,41]. Factors such as tissue damage and sheer force also prompt both EPCs and endothelial cells to transdifferentiate into VSM cells [42,43].…”
Section: Pericytes and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This switch is important during resolution of vascular injury and homeostasis and appears to be regulated by different miRNAs [38,39]. Chronic inflammation and tissue hypoxia are thought to induce increased vascular growth by directly effecting the VSM cells [40] the result being muscularisation and thickening of the blood vessels [13,40,41]. Factors such as tissue damage and sheer force also prompt both EPCs and endothelial cells to transdifferentiate into VSM cells [42,43].…”
Section: Pericytes and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Patients with COPD have an increased number of infiltrating CD8 + Tlymphocytes in adventitia in pulmonary arteries [41]. It has been shown that cigarette smoke may increase the number of circulating neutrophils in the blood vessels and in the airways, with neutrophils assembling in pulmonary capillaries, sputum and BALf [98].…”
Section: Inflammatory Cells In the Pulmonary Circulationmentioning
confidence: 99%
“…Previous studies have shown an increased number of inflammatory cells [8,9] in pulmonary arteries from patients with COPD. Inflammatory cells are a source of cytokines and growth factors that may contribute to the development of structural and functional abnormalities of the vessel wall [23].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, some of them would have been ventilated before lung transplantation. Since it is known that smoking and ventilation may induce structural changes in pulmonary arteries, this may have influenced the results [9,35,36]. TGF-b AND VERY SEVERE COPD B. BEGHE ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation